Insulation characteristic analysis of coconut oil and palm oil as liquid insulating material - Mohd Jamail, Nor Akmal; Ishak, M. H.; Muhamad, N.A. (United Kingdom Simulation Society, 2017)
The paper presents a study which has been carried out to use coconut oil as insulation in transformers. In transformer, oil is used as a coolant and also as an insulator. Nowadays, petroleum based oil is widely used in the transformer as it meets the requirements to be the best insulator. It is a fact that petroleum based oil will not be available for future generation used. Hence, further studies discovered that the coconut oil and refined, bleached, deodorized palm oil (RBDPO) has a great potential to be used a liquid insulation in transformer. An electrical test which using the breakdown voltage method was conducted for the coconut oil and refined, bleached, deodorized palm oil (RBDPO). The coconut oil and palm oil which have different heat effect were measured and compared to each other. The results shows that the coconut oil have high breakdown voltage compared to RBDPO. The result of the coconut oil and refined, bleached, deodorized palm oil (RBDPO) show that the samples have good insulation characteristic as liquid insulating material.